DIVERSIFIKASI PENDAPATAN ASLI DESA MELALUI BUMDES: ANALISIS PENGELOLAAN POTENSI LOKAL DI DESA KEBONTUNGGUL - Dewi Kumalasari; Siandi (LPPM Institut Agama Islam Uluwiyah Mojokerto, 2025)
Village-Owned Enterprises (BUMDes) play a significant role in increasing village revenue through the management of local resources. This study analyzes the diversification strategies of Village Original Income (PADes) implemented by BUMDes Kebontunggul in Mojokerto. A case study approach was applied using interviews, observations, and documentation. The findings show that agricultural units, tourism services, and microfinance activities contribute to PADes growth and local economic opportunities. The main challenges include limited managerial capacity and insufficient capital.